A Study on the Influence of Personality and Social Competencies on the Performance of Kindergarten Teachers Based on the Principal's Assessment (Universitas Negeri Semarang, 2020)
Having competencies can create work professionalism and are reflected in the teaching performance performed by a teacher. These competence components include personality and social competencies. This study aims to analyze the influence of personality and social competencies of Kindergarten teachers in their teaching performance based on the principal's assessment. The samples were 101 school principals who assessed 173 kindergarten teachers. The research method used was quantitative with ex-post facto design. The data were collected through a questionnaire with a Likert scale. To determine the accuracy of the model, classical assumption testing was done which included normality test, multicollinearity test, and heteroscedasticity test. The analysis technique used was multiple regression analysis both partially and simultaneously. The results show that: first, there was a positive and significant influence between personality competence toward teacher performance with a significance of 41.8%. Second, there was a positive and significant influence between social competence toward teacher performance with a significant percentage of 47.8%. Third, there was a positive and significant influence between personality and social competencies toward teacher performance with a significant percentage of 51.9%. Through the results of these studies indicate that personal and social competence plays a role in the formation of teachers' performance, so it’s important for teachers to always try improve their ability to produce more optimal performance.